Direct Laser Metal Deposition of AISI H13 Cladding on Copper–Beryllium Alloy Substrate Through a Stainless‐Steel Buffer Layer Strategy. Issue 4 (28th August 2022) - Zhao, Zhao; Perini, Matteo; Bosetti, Paolo; Pellizzari, Massimo
Abstract : AISI H13 cladding is deposited on the copper–beryllium (CuBe) alloy substrate by direct laser metal deposition via a buffer layer strategy. The SS316L austenite stainless steel is used as the buffer material attempting to reduce the risk of cracking. Single‐ and multi‐layer samples are deposited, including single‐layer SS316L, 1‐layer SS316L + 1‐layer H13, 2‐layers SS316L + 1‐layer H13, and 1‐layer SS316L + 4‐layers H13. The defect‐free single‐layer SS316L cladding is successfully deposited after the parameter pre‐optimization. Two types of defects including porosity and cracking are observed in all multi‐layer systems. The cladding microhardness of the 2‐layer system is rather low (400HV). A 50% increase in the cladding microhardness is observed when depositing on the five‐layer system. The five‐layer system shows a better load‐bearing capability (LBC) compared with the CuBe substrate in the low loading range. As load increases above 10 kN, the five‐layer cladding system shows the worse LBC compared to CuBe due to the low strength of the heat‐affected zone. A 2.7% cladding to substrate thickness ratio allows keeping more than 80% of the original thermal conductivity of the CuBe substrate. Abstract : Depositing defect‐free H13 cladding on copper–beryllium alloy substrate is a challenge. A buffer material SS316L is used to eliminate the cracks. The cracking mechanism is discussed. The benefits of this bimetallic structure are proved by the microhardness profiles, load‐bearing capability tests, and thermal conductivity calculation.